Diagnostic value of PET/CT with (11)C-methionine (MET) and (18)F-fluorothymidine (FLT) in newly diagnosed glioma based on the 2016 WHO classification - Ogawa, Tomoya (EJNMMI Res, 2020)
BACKGROUND: The molecular features of isocitrate dehydrogenase (IDH) mutation and chromosome 1p and 19q (1p/19q) codeletion status have pivotal role for differentiating gliomas and have been integrated in the World Health Organization (WHO) classification in 2016. Positron emission tomography (PET) with 3′-deoxy-3′-[(18)F]fluorothymidine (FLT) has been used to evaluate tumour grade and proliferative activity and compared with l-[methyl-(11)C]-methionine (MET) in glioma patients. Herein, we evaluated tracer uptakes of MET-PET/CT and FLT-PET/CT for differentiating glioma based on the 2016 WHO classification especially in relation to IDH1 mutation status. METHODS: In total, 81 patients with newly diagnosed supratentorial glioma were enrolled in this study. They underwent PET/CT studies with MET and FLT before surgery. The molecular features and histopathological diagnosis based on the 2016 WHO classification were determined using surgical specimens. The ratios of the maximum standardized uptake value (SUV) of the tumours to the mean SUV of the contralateral cortex (T/N ratios) were calculated on MET-PET/CT and FLT-PET/CT images. RESULTS: The mean T/N ratios of MET-PET/CT and FLT-PET/CT in IDH1-wildtype tumours were significantly higher than those in IDH1-mutant tumours (P < 0.001 and P < 0.001, respectively). Receiver operating characteristic analysis for differentiating IDH1 mutation status showed that the area under the curve of the FLT T/N ratio was significantly larger than that of the MET T/N ratio (P < 0.01). The mean T/N ratio of FLT-PET/CT in IDH1-wildtype tumours was significantly higher than that in IDH1-mutant tumours among grade II and III gliomas (P = 0.005), but this was not the case for MET-PET/CT. Both MET-PET/CT and FLT-PET/CT were able to distinguish between grade II and III gliomas in IDH1-mutant tumours (P = 0.002 and P < 0.001, respectively), but only FLT-PET/CT was able to distinguish between grade III and IV gliomas in IDH1-wildtype tumours (P = 0.029). CONCLUSION: This study showed that FLT-PET/CT can be used to determine the IDH1 mutation status and evaluate glioma grade more accurately than MET-PET/CT. FLT-PET/CT can improve glioma differentiation based on the 2016 WHO classification, but caution must be paid for tumours without contrast enhancement and further studies should be conducted with more cases.